Efficacy and safety of high dose accelerated intravenous iron sucrose in patients of iron deficiency anemia - Naik, Muzafar; Bhat, Tariq; Jalalie, Ummer; Bhat, Arif; Waseem, Mir; Tahir Ganayie, Mohd (International Journal of Research in Medical Sciences, 2017)
Background: Low dose (200 mg) extended Intravenous iron sucrose remains the most common treatment option in patients who are intolerant to oral iron therapy in patients with Iron deficiency anemia (IDA). The objective of this study was to evaluate the efficacy and safety of high dose accelerated intravenous iron sucrose (IS) in the treatment of adults with iron deficiency anemia Methods: One hundred adult patients with iron deficiency anemia, who had intolerance or showed no effect with oral iron therapy, received daily doses of 500 mg of intravenous iron sucrose until the hemoglobin level was corrected or until receiving the total dose of intravenous iron calculated for each patient. Results: The mean and median Hb (g/dL) 6.47±1.656 and 6.6 (2) at baseline, 9.61±1.629 and 9.6 (2) at 2 weeks of treatment, 11.85±1.277 and 12 (1) at 4 weeks of treatment respectively. The mean rise of Hb was 3.13±1.41 and 5.37±1.50 after 2 and 4 weeks of treatment respectively (p<0.000). A total of 303 intravenous infusions of iron sucrose were administered and iron sucrose was generally well tolerated with twenty-six patients developing mild and one patient developing moderate adverse drug reactions. There was no serious adverse event recorded. Conclusions: Accelerated high dose intravenous iron sucrose is a safe and cost effective option minimizing frequent hospital visits in the treatment of adults with iron deficiency anemia who are intolerant or lack satisfactory response to oral iron therapy.